Multiphase, Multiscale Chemomechanics at Extreme Low Temperatures: Battery Electrodes for Operation in a Wide Temperature Range. Issue 37 (21st August 2021) - Li, Jizhou; Li, Shaofeng; Zhang, Yuxin; Yang, Yang; Russi, Silvia; Qian, Guannan; Mu, Linqin; Lee, Sang‐Jun; Yang, Zhijie; Lee, Jun‐Sik; Pianetta, Piero; Qiu, Jieshan; et al.
Abstract: Understanding the behavior of lithium‐ion batteries (LIBs) under extreme conditions, for example, low temperature, is key to broad adoption of LIBs in various application scenarios. LIBs, poor performance at low temperatures is often attributed to the inferior lithium‐ion transport in the electrolyte, which has motivated new electrolyte development as well as the battery preheating approach that is popular in electric vehicles. A significant irrevocable capacity loss, however, is not resolved by these measures nor well understood. Herein, multiphase, multiscale chemomechanical behaviors in composite LiNi x Mn y Co z O2 (NMC, x + y + z = 1) cathodes at extremely low temperatures are systematically elucidated. The low‐temperature storage of LIBs can result in irreversible structural damage in active electrodes, which can negatively impact the subsequent battery cycling performance at ambient temperature. Beside developing electrolytes that have stable performance, designing batteries for use in a wide temperature range also calls for the development of electrode components that are structurally and morphologically robust when the cell is switched between different temperatures. Abstract : A holistic experimental approach is adopted to systematically elucidate the multiphase, multiscale chemomechanical behaviors in LIB cathodes at extremely low temperatures. The results suggest that, in order to design batteries for use in a wide temperature range, it is critical to develop electrode components that are structurally and morphologically robust when the cell is switched between different temperatures.